An Illusion of Interactivity: The paternalistic side of data journalism. (16th March 2018) - Appelgren, Ester
Abstract : This study explores paternalism in contemporary data journalism, a hybrid form of journalism where parts of the engineering culture are blended with the culture of journalism. Technologists often question paternalistic elements in design, whereas journalists consider paternalistic decision-making to be justified as an inherent part of what journalism is. Based on a predominately qualitative content analysis of paternalistic elements in 31 data journalistic projects submitted to the Nordic Data Journalism Awards in 2013, 2015 and 2016, three characteristics of paternalism were found: controlling functionality, the illusion of interactivity and linearity. All three characteristics include several types of control over the audience control, embedded in the design, and as previous research has found that paternalism is often associated with negative effects, on the basis of journalistic choices in design and presentation involving technology, the problem is whether the audience begins to perceive data journalism as controlling, non-transparent or intrusive.